Relationship between Parent Characteristics and Economic Status with Nutritional Status among Toddlers 0-24 Months in Sumedang - Muhamad Jehan Ramadhan; Nashilah Musyaropah; Isti Kumalasari; Asti Dewi Rahayu; Muchamad Rizki Sentani (Universitas Pendidikan Indonesia, 2023)
Introduction: Nutritional status serves as a gauge to depict an individual's dietary well-being, stemming from the equilibrium between nutritional requirements and the intake of essential nutrients necessary for sustained bodily metabolism. The aim of this research is to analyze the characteristics of families with incidents of malnutrition, stunted, and waste in children aged less than two years in Sukamandiri Village, Sumedang Regency.Method: The research used a cross-sectional design with 117 toddlers selected using a purposive technique. The instruments were questionnaires, weight scales, and microtoise. The assessment was categorized by weight/age, height/age, and weight/length. The relationship between variables was analyzed using the chi-square test.Result: The results of the study stated that there were no characteristic variables that were related to malnthe utrition of toddlers. The factor related to the incidence of stunted toddlers is the mother's occupation as evidenced by the p-value = 0.000 (p 0.05). Father's educational background was associated with wasted toddlers (p-value = 0.045; p0.05). It is needed for local government to increase the socio-economic status of families in controlling nutritional problems in the future.